2021
DOI: 10.1088/2053-1591/abfba5
|View full text |Cite
|
Sign up to set email alerts
|

An insight into advance self-healing composites

Abstract: The purpose of the investigation is to review self-healing mechanisms and various advanced self-healing materials which are recently used for repairing composite materials. The manufacturing and characterization processes are studied in depth for self-healing carbon fiber reinforced composites, microcapsules, and supra-molecular elastomers. The composite structures fail due to internal cracks. These cracks are initiated due to continuous loading of structures. It is not possible to fill those cracks especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…It can be observed that almost all the regions were filled with healing agents and strong nylon connections were seen all over the structures [ 206 ].…”
Section: Fiber-reinforced Epoxy Self-healing Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that almost all the regions were filled with healing agents and strong nylon connections were seen all over the structures [ 206 ].…”
Section: Fiber-reinforced Epoxy Self-healing Compositesmentioning
confidence: 99%
“…The technical qualities of the product are restored by using enough liquid resin as a curing representative to cover the break opening completely. Even though this device requires mending agent channels, and continuous self-healing inside the polymer composite is not possible, the benefit of autonomous self-healing is the absence of external engagement in the treating process [ 206 , 207 , 209 ].…”
Section: Fiber-reinforced Epoxy Self-healing Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…This process inevitably causes premature solidification of other unbroken microcapsules, which means that most microcapsule composites can only repair such damage once, or at best several times before becoming completely useless. [20][21][22][23] In addition, the healing agent contained in the microcapsules is released passively after the rupture of the shell triggered by the external stimulation, which causes problems such as failed shell cracking, delayed release, and low healing rates. [24][25][26][27][28][29] Finally, the microcapsule shell, which serves as a container, dramatically deteriorates the insulating characteristics of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Friction brakes are the most popular braking mechanism in commercial or special-purpose vehicles [17][18][19][20]. They're often rotating devices with a spinning wear surface, such as a disc or drum, and a stationary pad or shoe [21][22][23].…”
Section: Introductionmentioning
confidence: 99%